Influência de diferentes concentrações de enzimas lactase e temperaturas sobre a hidrólise da lactose em leite pasteurizado - Trevisan, Ana Paula (2008)
The intolerance to lactose is the most common intolerance to carbohydrates among people of all ages and it affects about 70% of the adult population worldwide. Due to the prevalence of this condition on the world population, the commercial interest on milk and derivatives with reduced amount of lactose has increased. Such product can be obtained through lactose hydrolysis, mainly through the enzymatic method, using lactase enzyme. The level of lactose hydrolysis depends on the dosage of J-galactosidase in milk, as well as on its processing conditions and, for this reason, it is extremely important to evaluate the influence of such conditions concerning obtainment of milk with reduced amount of lactose, such as temperature during hydrolysis and lactase concentration, over the efficiency of the hydrolysis process and over the physical, chemical and microbiological characteristics of the fina product. The aim of the present study was to observe the influence of different temperatures and concentrations of lactase enzymes over the lactose hydrolysis in pasteurized milks. Samples of pasteurized milks from the Usina Escola de Laticínios (UFSM) were used. Lactase enzyme, supplied by two companies, was added to the milk in different quantities (0.1g/L; 0.2g/L; 0.5g/L; 0.8g/L e 0.9g/L) and hydrolysis was accomplished in different temperatures (7.9ºC; 12ºC; 22ºC; 32ºC e 36.1ºC). These two variables were combined through Response Surface Methodology (RSM) by rotational composed central delineation. Hydrolysis was followed by crioscopy until it reached stabilization. Physical, chemical and microbiological analysis were carried out before and after lactose hydrolysis, and sensorial analysis was carried out after hydrolysis. Lactase enzyme input modified physical and chemical properties and characteristics of milk, reducing pH, crioscopy, fat and lactose levels and increasing density, total dry extract (TDE), free-fat dry extract (FDE), glucose and protein levels. There was a difference between the efficiency of the two enzymes on the reduction of the lactose level. Lactose hydrolysis reached values in between 80% and 100%, reducing lactose level to less than 1g/100g, thus enabling milk ingestion by individuals who are intolerant to this carbohydrate. Higher percentages of hydrolysis and, consequently, lower lactose levels were verified in temperatures in between 15 and 30°C, using enzyme concentrations in between 0.6 and 1.0 g/L. The average total count after hydrolysis was beyond the limit established by law, but concerning the count per milk sample, using enzyme 1 and 2, treatments three and seven did not exceed this limit, respectively. Higher values of total count were found at the highest temperatures and using lowest enzyme concentrations. Differences among milk samples with different lactose levels were not sensorially perceived through triangular test.